Leaving Home: Decoding Art Projects of Female Arab-Palestinian Students. (2nd January 2021) - Marnin-Distelfeld, Shahar; Meler, Tal
Abstract : This article examines projects of female Arab-Palestinian college art students in the Israeli periphery. The projects focus on the students' living environment, domestic space, and the transition from their childhood home to the new post-marriage house. They experience this transition, which usually also means leaving the familiar environment of their village of origin for another place, as a significant step that involves mixed feelings of self-fulfillment through marriage and the pain of separating from their childhood homes. A qualitative analysis of the projects relying on a methodology of visual interpretation and interviews with the students revealed their ambivalent attitude towards this step. Findings showed that the projects reflect a gendered geography related to the perception of domestic space. The students express an intermediate position of "individualized traditionalism, " compatible with their choice to describe the domestic space as embodying a tension between conservative perceptions of marriage and personal reflections on marriage. It was also found that the projects reflect a "low gaze, " a downward view on the students' part when they observe the world around them through familiar and concrete objects and limited spaces while practicing art. Their observations emanate from both a state of belonging and an external and critical perspective. Their choice of a realistic-naive painting style and depictions devoid of human figures emphasizes the cultural and gender caution they display when expressing their position, echoing the perceptions of their society.